2022
DOI: 10.1021/acssuschemeng.2c04356
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immunoprobe Based on MOF-818 Synergizing with an Antifouling Sensing Interface to Improve Immunosensors

Abstract: Sensitivity and accuracy are both of great significance for immunosensors in practical application; thus, it is an effective strategy to improve the performance of immunosensors from the above two aspects. Herein, we reported a multifunctional immunoprobe based on metal−organic framework 818 (MOF-818) that possessed dual catalytic activity to enhance the sensitivity of immunosensors. In the presence of dopamine and hydrogen peroxide, MOF-818 can accelerate the oxidative polymerization of dopamine to couple bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The strong hydrophilicity of PEG was utilized to form a dense hydration layer, which effectively reduced the adsorption of non-specific proteins on the electrode surface and achieved the expected anti-fouling effect. The results showed that when human serum epididymal protein 4 (HE-4), human immunoglobulin (IgG), carcinoma antigen 125 (CA12-5), and neuron-specific enolase (NSE) were selected as interferences, the corresponding currents produced were negligible [46]. The fabrication process of the electrochemical immunosensor is shown in Figure 1.…”
Section: Polyethylene Glycol (Peg) and Its Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong hydrophilicity of PEG was utilized to form a dense hydration layer, which effectively reduced the adsorption of non-specific proteins on the electrode surface and achieved the expected anti-fouling effect. The results showed that when human serum epididymal protein 4 (HE-4), human immunoglobulin (IgG), carcinoma antigen 125 (CA12-5), and neuron-specific enolase (NSE) were selected as interferences, the corresponding currents produced were negligible [46]. The fabrication process of the electrochemical immunosensor is shown in Figure 1.…”
Section: Polyethylene Glycol (Peg) and Its Derivativesmentioning
confidence: 99%
“…In most cases, the method used to reduce non-specific adsorption involves applying anti-fouling materials directly onto the electrode's surface. These materials include PEG and its derivatives [44][45][46][47][48][49], zwitterionic polymers [41,[50][51][52], peptides [53][54][55][56][57], and hydrogels [58][59][60][61], among others [62][63][64]. A new method has been developed in recent years, whereby the immunorecognition and signal readout platforms are separated, and the anti-fouling material is used to modify magnetic beads instead of the electrode's surface, resulting in good conductivity of the electrode [65][66][67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of proteins, EC assays can analyze samples with target concentrations 5−6 orders of magnitude lower than traditional ELISA. 22,23 However, most existing EC methods are still unable to accurately detect trace amounts of protein. They also face the challenges of multistep handling and biofouling at the electrode interface, which results in nonspecific high background noise and risk of false positives.…”
mentioning
confidence: 99%
“…EC assays provide a powerful and promising tool for the development of sensitive detection of proteins due to their rapidity, robustness, sensitivity, cost-effectiveness, and environmental insensitivity toward electroactive labels. With the impressive sensitivity demonstrated so far, they have the potential to replace ELISA in certain applications, especially those involving point-of-care testing and in vitro diagnosis. In the case of proteins, EC assays can analyze samples with target concentrations 5–6 orders of magnitude lower than traditional ELISA. , However, most existing EC methods are still unable to accurately detect trace amounts of protein. They also face the challenges of multistep handling and biofouling at the electrode interface, which results in nonspecific high background noise and risk of false positives.…”
mentioning
confidence: 99%